Diseño de una planta de agua potable para la Ciudad de Machala - Espinoza Mendieta, Andrea Estefania (Machala : Universidad Técnica de Machala, 2021)
According to the INEC, the city of Machala had a population of 256,022 inhabitants until 2010. Taking into account that the demand for drinking water increases as the city develops; Therefore, the main objective of this research work is to design a drinking water plant for the city of Machala by means of a bibliographic search. To carry out a population estimate, 3 methods were used: arithmetic, geometric and mixed. With this last method, a projection of 296,406 inhabitants was obtained for the year 2030. Based on this projection, a flow of 1.22 m3 / s was used. Regarding the characterization, parameters were taken into account according to the CPE INEN 5 Part 9-1 standard for the effluent and, for the effluent, the NTE INEN 1108 standard was used. For the determination of operations of the plant, type C water was considered as a tributary whose characteristics are: average turbidity less than 150 NTU and NMP less than 5000 fecal coliforms / 100 ml. According to this type of water, the following operations were designed: a pre-treatment with mechanical cleaning grids that, like simple settlers, were proposed with two units at a flow rate of 0.61 m3 / s, slow filters for which 220 units were used with 99 m2 of surface area and a flow rate of 0.0055 m3 / s; finally, a chlorination tank was designed considering a dose of 2 mg / l of sodium hypochlorite.
La ciudad de Machala de acuerdo a la INEC poseía una población de 256 022 habitantes hasta el año 2010. Teniendo en cuenta que la demanda de agua potable aumenta conforme la ciudad se desarrolla; por lo tanto, en el presente trabajo de investigación se tiene como objetivo principal diseñar una planta de agua potable para la ciudad de Machala mediante búsqueda bibliográfica. Para realizar una estimación poblacional se emplearon 3 métodos: aritmético, geométrico y mixto, con este último método se obtuvo una proyección de 296 406 habitantes para el año 2030. En base a esta proyección se trabajó con un caudal de 1.22 m3/s. Con respecto a la caracterización, se tomaron en cuenta parámetros de acuerdo a la norma CPE INEN 5 Parte 9-1 para el afluente y, para el efluente se empleó la norma NTE INEN 1108. Para la determinación de operaciones de la planta se consideró un agua tipo C como afluente cuyas características son: turbiedad media menor a 150 UNT y NMP menor a 5000 coliformes fecales/ 100 ml. Según este tipo de agua se diseñaron las siguientes operaciones: un pretratamiento con rejillas de limpieza mecánica que al igual que los sedimentadores simples se plantearon con dos unidades a un caudal de 0.61 m3/s, filtros lentos para lo cual se emplearon 220 unidades con 99 m2 de área superficial y un caudal de 0.0055 m3/s; finalmente se diseñó un tanque de cloración considerando una dosis de 2 mg/l de hipoclorito de sodio.
Keywords: POTABILIZACION; CARACTERIZACION; DISEÑO; AFLUENTE